GERMAN POSITION TOWARDS UKRAINE CRISIS WITHIN THE CONTEXT OF EUROPEAN SECURITY PROBLEMS AND RELATIONS WITH THE RUSSIAN FEDERATION - O. Yu. Semenov; D. A. Belashchenko (Вестник Кемеровского государственного университета, 2015)
The paper analyzes latest crisis events in Ukraine within the context of contemporary German-Russian relations as well as European security problems. The purpose of the paper is to reveal the peculiarities of conceptual position as well as practical German steps towards Ukraine crisis taking into account continental security problems and RussianGerman dialogue dynamics. The paper methodology includes the principles of historicism, objectivity, systemic, concreteness as well as methods of historical and political research: synchronous, chronological, comparative benchmarking, source analysis techniques, event analysis, historical induction and deduction. The results of the paper include new scientific data on the specific German position towards latest Ukrainian events. It is pointed out that Berlin foreign policy, aimed at hard counteractions to Russian ideas and interests and formed well under external influence, needs to be reformatted otherwise such policy may weaken both internal and foreign positions of German Chancellor A. Merkel. The paper outcomes may be used by Russian state authorities when elaborating new technologies of effective use of bilateral diplomacy tools as well as taking part in constructing common European security architecture.